2017
DOI: 10.1007/s40095-017-0244-6
|View full text |Cite
|
Sign up to set email alerts
|

Heat pumps in subarctic areas: current status and benefits of use in Iceland

Abstract: Heat pumps use the temperature difference between inside and outside areas to modify a refrigerant, either for heating or cooling. Doing so can lower the need for external heating energy for a household to some extent. The eventual impact depends on various factors, such as the external source for heating or cooling and the temperature difference. The use of heat pumps, and eventual benefits has not been studied in the context of subarctic areas, such as in Iceland. In Iceland, only remote areas do not have ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…With the rise of energy costs and technological advancements, heat pumps are now being reconsidered as an alternative heating system [5]. The efficiency of heat pumps in subarctic areas are stated in [6].…”
Section: Introductionmentioning
confidence: 99%
“…With the rise of energy costs and technological advancements, heat pumps are now being reconsidered as an alternative heating system [5]. The efficiency of heat pumps in subarctic areas are stated in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Heat pumps, and specifically ASHPs, are becoming more capable and efficient. A study of 128 heat pumps installed in Icelandic homes found an energy savings of approximately 30% annually [4]. Average temperatures in Reykjavik are a few degrees Celsius warmer than those in Windsor or Toronto, Ontario [4,16].…”
Section: Introductionmentioning
confidence: 99%
“…A study of 128 heat pumps installed in Icelandic homes found an energy savings of approximately 30% annually [4]. Average temperatures in Reykjavik are a few degrees Celsius warmer than those in Windsor or Toronto, Ontario [4,16]. ASHPs studied in Alaska were found to require backup heating only at very low temperatures and to have operating ranges extending to − 27 • C [56].…”
Section: Introductionmentioning
confidence: 99%